Comparison of two social activities - Košarac, Biserka R. (Sociološki pregled, 2020)
The work gives an analysis of the monograph Dobrica Ćosić between Politics and Literature written by Zoran Avramović, PhD. The first part presents the structure of the monograph and basic theoretical frameworks from which the author starts in his study of the relation between Dobrica Ćosić’s literary work and political activities. It is followed by the consideration of the study and the arguments proving that Ćosić did not affect his literary work by his political views and engagement, and, as the author of this monograph claims, that we may speak about one Ćosić in literature and another in politics.
Keywords: Dobrica Ćosić; literature; politics; culture